An Oral History of Programming Practices: Gender and Age Dynamics and Digital (Dis)Engagement Among Computer Programmers in Finland - Silvast, Antti (Human Technology, 2015)
Since the 1980s, educational policies in many countries have aimed at improving the computer literacy and programming competencies of the population. Over the same period, the possibilities that people have seen regarding programming and everyday programming practices have emerged as an area of strong interest within historical scholarship. The paper contributes to these discussions by drawing on techniques of oral history to focus on programming hobbies and practices in Finland. Examining data from a massive survey of computer hobbyists (N = 1,453) and their recollections about personal computer use (largely during the 1980s), the paper gathers new information on what leads to people’s pursuit of or interest in programming and how their programming habits have changed over time. The study links together the gender and age dynamics in programming and shows how the respondents not only engaged with but also could become disengaged from programming for various reasons.